Assessment of proliferation markers in metastatic melanoma in sentinel lymph nodes. Issue 12 (6th September 2011) - Joannou-Coetzee, André; Villena, Noranette; Powell, Barry W E M; Cook, Martin G
Abstract : Aim: Some views on sentinel nodes for melanoma seem to cast doubt on the relevance of micrometastases in the sentinel nodes of patients with melanoma, suggesting that small metastases or isolated tumour cells can be ignored. Tumour dormancy has been proposed for their postulated lack of progression. The implication of the argument seems to be that minute metastases are inactive and therefore non-threatening, whereas larger ones are proliferative and therefore have aggressive potential. Methods: 54 sentinel lymph nodes were studied with histologically identified micrometastatic melanoma using the protocol accepted by the European Organisation for Research and Treatment of Cancer melanoma group. These were studied with respect to metastasis size and by use of immunohistochemical markers of proliferation (MIB-1) and dormancy (p16). Results: The authors have demonstrated no correlation between the size of metastases and their proliferative activity. Very small metastases may not show proliferative activity, but this may be a reflection of the small number of assessable cells rather than a genuine reflection of the tumoural characteristics. Furthermore, the minute size of some of these metastases resulted in no residual tumour being present in adjacent sections. Where further sections did show more tumour, these small metastases were invariably p16 negative, suggesting dormancy was not the explanation for the lack of measurable proliferation. Occasionally, larger metastases, clearly not clinically insignificant, showed no proliferative activity presumably, considering their size, a transient phenomenon. Conclusion: These findings suggest that variable phases in proliferation occur in metastases, and no conclusion of clinical insignificance can be made on the basis of small size.